A medida de proteção na lei Maria da Penha: um estudo sobre a evolução de sua natureza jurídica, de sua importância e de sua aplicação nas empresas familiares - Pagliuso, Ricardo Palacin (2024)
Gender-based violence is a deeply rooted and persistent social problem that continues to plague societies around the world. Women everywhere continue to be victims of various forms of violence, undermining their dignity, equality and fundamental human rights. In the Brazilian context, this problem is not an exception and the Maria da Penha Law, formally known as Law nº 11,340/2006, represents an important instrument to combat this complex and devastating issue. This dissertation's central objective is to deepen the study of the Maria da Penha Law, with a particular focus on the analysis of urgent protective measures. Through a broad and detailed exploration of these measures, we sought to understand their importance, evolution over time and effectiveness in protecting victims of gender-based violence in Brazil, always from the perspective of their legal nature. The aim is to assess the (im)possibility of its application in the business sector, particularly in family businesses. Through a meticulous analysis and evaluation of the legal changes introduced by Law No. 14,550/2023, this dissertation seeks to demonstrate that these measures transcended the barriers of rhetoric and became effective tools to combat gender-based violence in Brazil. The conclusion goes beyond the mere recapitulation of facts and analysis. We sought to understand the profound impact of urgent protective measures in the legal sphere. These measures are more than just legal provisions; They are a shield amid the storm of gender-based violence, representing society's commitment to protecting, supporting and restoring the dignity of victims. It is clear that urgent protective measures are not only legal devices, but also symbols of hope and justice for victims. To increase the work, the hypothetical-deductive method was used, through the qualitative technique, with documentary analysis of legal texts, national jurisprudence, in addition to national and international bibliography on the topic.